Effects of the TiC nanoparticle on microstructures and tensile properties of selective laser melted IN718/TiC nanocomposites - Yao, Xiling (2018)
The purpose of this paper is to investigate the effects of TiC nanoparticle content on microstructures and tensile properties of the IN718/TiC nanocomposites fabricated by selective laser melting (SLM). 0.5wt%, 1.0wt%, and 2.0wt% of TiC nanoparticles are added to the IN718 powders. The bulk-form IN718/TiC nanocomposites with different TiC contents are fabricated in-situ by SLM using the same process settings. The evolution of microstructures and tensile properties as the effect of changing the TiC content is studied using the optical microscopy, scanning electron microscopy, X-ray diffraction analysis, and tensile testing. The increase of TiC content refines the microstructure, promotes the formation of the cellular morphology, and reduces the size and continuity of Laves precipitates. Increasing the TiC content improves the yield strength and ultimate tensile strength but decreases the ductility. The grain refinement, dislocation bowing, dislocation punching, and the reduction in Laves precipitate contribute to the strengthening effect in the IN718/TiC nanocomposites.